2023
DOI: 10.1111/ggi.14571
|View full text |Cite
|
Sign up to set email alerts
|

Lower cognitive function as a risk factor for anemia among older Japanese women from the longitudinal observation in the SONIC study

Abstract: Aim The aging‐related increase in the incidence of anemia potentially affects the mortality risk. Lower cognitive function is common among older adults, and anemia is one of the causes of cognitive decline. However, to the best of our knowledge, no study has investigated whether cognitive decline is a risk factor for anemia in older people. Therefore, in this study, we used a 3‐year longitudinal evaluation to examine the association of cognitive function with anemia in community‐dwelling older adults. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Lifestyle factors, including malnutrition, smoking, alcohol consumption, and insufficient exercise, are considered important risk factors for anemia, which increases the risk of cognitive impairment (Paramastri et al, 2021 ). A recent study revealed that older Japanese women with lower scores on the Montreal Cognitive Assessment experienced a higher risk for anemia 3 years later, and researchers suggested that a healthy lifestyle might be important to prevent anemia (Noma et al, 2023 ). However, whether a healthy lifestyle in older adults can alleviate the adverse effects of anemia on cognitive function has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle factors, including malnutrition, smoking, alcohol consumption, and insufficient exercise, are considered important risk factors for anemia, which increases the risk of cognitive impairment (Paramastri et al, 2021 ). A recent study revealed that older Japanese women with lower scores on the Montreal Cognitive Assessment experienced a higher risk for anemia 3 years later, and researchers suggested that a healthy lifestyle might be important to prevent anemia (Noma et al, 2023 ). However, whether a healthy lifestyle in older adults can alleviate the adverse effects of anemia on cognitive function has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%